Character Education in Project-Based Learning to Foster Student’s Scientific Literacy and Independent Character - Ni Made Dyan Anggraeni; I Gede Astawan; Arina Zaida Ilma (Mimbar Ilmu, 2025)
This study addresses the problem of low scientific literacy and learning independence among students. One of the main contributing factors is the lack of a holistic approach in science education. The study aims to examine the effectiveness of the Project-Based Learning (PjBL) model integrated with character education in fostering scientific literacy and student independence in the Primary School Teacher Education (Pendidikan Guru Sekolah Dasar/PGSD) program. The study employed a quasi-experimental method with a non-equivalent posttest-only control group design. The independent variable was the instructional model (PjBL integrated with character education versus conventional learning), while the dependent variables were scientific literacy and student independence. The population of this study consisted of second-semester students from seven classes, with two classes selected through group random sampling, one as the experimental group and one as the control group. Data on scientific literacy were collected through a test, while student independence was measured using a questionnaire. Data were analyzed using descriptive and inferential statistics with MANOVA. The results revealed significant differences, both simultaneously and partially, between students taught using the PjBL model integrated with character education and those taught through conventional methods. The integrated PjBL model proved to be more effective in improving students’ scientific literacy and independence. The practical implication of this study is that educators may integrate character education into project-based learning to strengthen scientific literacy while fostering student independence.